The contribution of Nishkama Karma in the philosophies of Shankara, Ramanuja, and Madhva on social cohesion - Sukdaven, Maniraj (University of Pretoria, 2022)
Thesis (PhD (Science of Religion))--University of Pretoria, 2022.